Material Planning and Inventory Control in the Nutrition Service Unit at Ummi Hospital Bogor - Kartikasari, Maya Andini (Institut Ilmu Sosial dan Manajemen Stiami, 2024)
Inventory management is a critical component of supply chain management that involves the planning, controlling, and overseeing of inventory levels to ensure the availability of materials while minimising costs. Proper inventory management ensures that essential food supplies are always available, allowing the hospital to provide consistent and varied meal options tailored to patient needs. Effective inventory management also ensures that there are no disruptions in meal service due to stockouts and avoids the capital and storage issues related to overstocking. This study aims to provide solutions to hospitals in terms of planning and controlling materials for the 2024 budget year so that hospitals can improve in terms of inventory management. The economic order quantity model is used to determine the optimal number of orders to be made to maintain inventory at a certain level while optimising inventory costs. The result showed that the optimal order quantity for chicken meat is 41 kg, beef is 21 kg, and rice is 112 kg, and the inventory cost incurred due to the stock is Rp. 170,000, Rp. 268,000, and Rp. 191,400, respectively.